Does Loss of Immunohistochemical Expression of Glypican 3 in Oral Squamous Cell Carcinoma Play a Role in the Wnt/β-catenin Signaling Pathway?. Issue 9 (October 2021) - Jot, Kiran; Urs, Aadithya B.; Kumar, Priya
Abstract : Glypican 3 (GPC3) is a cell membrane protein and plays a dual role, as a tumor suppressor and oncogene, depending on its structure. It is known to regulate the Wnt/β-catenin signaling pathway and affect cell growth and proliferation. β-catenin plays a major oncogenic role in progression of oral squamous cell carcinoma (OSCC); thus, this study aimed to explore the relationship between β-catenin and GPC3 in OSCC. Immunoexpression of GPC3 and β-catenin was evaluated semiquantitatively in tumor tissue (n=80) and normal oral mucosa tissue (n=20). For GPC3, the percentage of stained cells and the staining intensity were assessed. For β-catenin, the percentage of stained cells, localization, and intensity of staining were assessed at the tumor-invasive front. The Pearson correlation was used to determine the correlation between the GPC3 and β-catenin immunoreactivity. Significantly decreased expression of GPC3 ( P =0.008) and a highly significant difference in the case of localization of β-catenin ( P =0.0001) were observed in OSCC when compared with normal oral mucosa. Cytoplasmic expression with a shift of β-catenin expression to the nucleus was seen in OSCC in comparison with primarily membranous and membranous and cytoplasmic staining in normal mucosa. A significant difference was observed with respect to localization of stain, with β-catenin staining moving to the nuclear compartment with an increase in the tumor grade ( P =0.011). No correlation was observed between β-catenin and GPC3 expression in OSCC cases. It is concluded that loss of expression of GPC3 in OSCC compared with normal oral mucosa indicates that it plays the role of a tumor suppressor gene in OSCC and its expression is therefore silenced in OSCC.